2017
DOI: 10.17221/14/2016-pps
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of endophytic bacteria from a desert plant Lepidium perfoliatum L.

Abstract: Li Y., Cheng C., An D. (2017): Characterisation of endophytic bacteria from a desert plant Lepidium perfoliatum L. Plant Protect. Sci., 53: 32-43.Sixty-two endophytic bacteria from the leaves, roots, and stems of healthy Lepidium perfoliatum L. were isolated and characterised. From the results, 89, 87, 90, and 97% isolates could tolerate 12% NaCl, 30% PEG 6000, 50°C and pH 10, respectively. 74% isolates could form a biofilm. Besides, 28 isolates could improve the germination rate of host seeds under different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…All the endophytes investigated in the present study resisted water stress at 20% PEG, with 82% of the endophytes exhibiting tolerance at 40% PEG ( Figure 2 ). Similarly, all 62 bacteria isolated from Lepidium perfoliatum [ 29 ], and 16 fungi endophytes isolated from Triticum aestivum [ 30 ] grew in media culture containing 20% PEG. However, unlike the fungi isolated from E. obtisufolius , the fungi isolated from wheat could not survive at a 40% PEG concentration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the endophytes investigated in the present study resisted water stress at 20% PEG, with 82% of the endophytes exhibiting tolerance at 40% PEG ( Figure 2 ). Similarly, all 62 bacteria isolated from Lepidium perfoliatum [ 29 ], and 16 fungi endophytes isolated from Triticum aestivum [ 30 ] grew in media culture containing 20% PEG. However, unlike the fungi isolated from E. obtisufolius , the fungi isolated from wheat could not survive at a 40% PEG concentration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Vigani et al (2019) found that root endophytic bacteria conferred drought resistance in Capsicum annuum by modifying vacuolar H + pyrophosphatases (VPP) expression, which aided in preserving osmotic balance. Strains of Bacillus endophytes found in Lepidium perfoliatum roots were responsible for the formation of biofilm on roots, resulting in drought resistance and seedling germination (Li et al, 2017). Piriformospora indica, a wellknown root fungal endophyte, colonizes the roots of many plant species and provides multifaceted amenities, including drought alleviation (Gill et al, 2016).…”
Section: Microbiome Drivers Of Plant Fitness Benefits Under Droughtmentioning
confidence: 99%
“…Many plant growth promoting bacteria have been reported to increase the drought resistance in plants like Pisum sativum, Zea mays, Vigna radiata, Triticum aestivum, Capsicum annum, Solanum tuberosum and Sorghum bicolor (Sandhya et al 2017;Yuanting et al 2017;Susilowati et al 2018;Niu et al 2018;Marulanda et al 2009). Based on these, much more candidate organisms can be well expected from stress adapted plants like A. comosus.…”
Section: Introductionmentioning
confidence: 99%